The Constellations - Cunningham, Kevin, 1966- (Book collections on Project MUSE., 2012)
Itu2019s 1974 in DeKalb County, Illinois and the planets have failed to align for Roy Conlon. Widowed and broke, his eight-year-old son Eric is suddenly a mystery to him. The boy has become aware of a sky awhirl with stars and of the universe outside his small-Midwestern town. And as powerful forces pull Eric away, Royu2019s efforts to hold onto his son are threatened by weakness, guilt, and his participation in a foolish crime.